Optimizing Digital Marketing Platform for the Success of Asnaf Entrepreneurs - Nuryati, Marita Sri; Bahri, Efri Syamsul (Yayasan Mitra Peduli Indonesia, 2022)
The COVID-19 pandemic has had an impact on the global economy. One entity that is affected by the household economic sector is Asnaf Entrepreneurs. To overcome this problem, the managing entity of Asnaf Entrepreneurs needs to facilitate digital marketing to help its success. This study aims to identify digital marketing platforms that can succeed as Asnaf Entrepreneurs and their optimization strategies. This study is qualitative research with a descriptive approach. Data and references were obtained from literature studies. The analysis was done descriptively and content analysis. The study results found that digital marketing platforms for Asnaf Entrepreneurs include: Facebook, Path, Instagram, Twitter, Linkedin, Youtube, Whatsapp, Google, FB Messenger, Line, BBM, Pinterest, and Wechat. The strategy for implementing the use of digital platforms can be done through training and mentoring. Besides, the Asnaf Entrepreneurs management entity needs to facilitate Asnaf Entrepreneurs with digital marketing facilities. Thus, the competencies obtained in training and mentoring can be realized in improving business performance. However, Asnaf Entrepreneurs have contributed to national development. So, the transformation process needs to be carried out on an ongoing basis. It is in order to advance to Muzakki as a Zakat payer